2011
DOI: 10.1007/s11926-011-0227-1
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Lupus Anticoagulants and Antiphospholipid Antibodies

Abstract: Lupus anticoagulants (LA) are immunoglobulins (IgG, IgM, and/or IgA) which interfere with one or more of phospholipid-dependent in vitro coagulation tests, eg, activated partial thromboplastin time (aPTT), kaolin clotting time (KCT), dilute Russell viper venom time (dRVVT), and dilute prothrombin time (dPT). LAs may be seen in a variety of clinical settings including the primary antiphospholipid syndrome (APS), systemic lupus erythematosus (SLE), other autoimmune diseases, secondary to infections, malignancies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 81 publications
(140 reference statements)
0
30
0
1
Order By: Relevance
“…Anti-β2-GPI consist in a heterogeneous group of antibodies, only a few of which are responsible for tissue damage. When associated with infections or drug exposure, these antibodies may have no pathogenic role (Shoenfeld et al, 2003; Sène et al, 2008; Dlott and Roubey, 2012). As a functional test, LAC is the most powerful predictor of pathology in APS (Galli et al, 2003).…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-β2-GPI consist in a heterogeneous group of antibodies, only a few of which are responsible for tissue damage. When associated with infections or drug exposure, these antibodies may have no pathogenic role (Shoenfeld et al, 2003; Sène et al, 2008; Dlott and Roubey, 2012). As a functional test, LAC is the most powerful predictor of pathology in APS (Galli et al, 2003).…”
Section: Diagnosismentioning
confidence: 99%
“…The hepatitis C virus, human immunodeficiency virus (HIV), human herpes virus, adenovirus, and parvovirus B19 are the most common viral infections related to aPL detection; aPL can be also detected in bacterial diseases, such as leprosy and syphilis (Sène et al, 2008). Procainamide, phenothiazines, quinine, oral contraceptives, and anti-TNF agents are the drugs that may induce generation of aPL (Ramos-Casals et al, 2008; Dlott and Roubey, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that platelet aggregation is enhanced via 5HT2A antagonism by SGAs, or due to hyperhomocysteinemia [13]. Moreover, typical antipsychotics, especially phenothiazines, and clozapine, have been implicated in the induction of antiphospholipid antibodies [23]. Hyperprolactinemia has been recently found to cause Adenosine-Diphosphate-(ADP-) stimulated platelet activation [16].…”
Section: Discussionmentioning
confidence: 99%
“…35 The opsonization of dying cells that express negatively charged phospholipids on their surface has been suggested as a third circumstance that can induce autoantibodies against β2-GPI. 36 Many drugs have been linked to the generation of antiphospholipid antibodies, 37 of which procainamide-induced autoantibodies account for the highest association with thrombotic complications. 38 It is known that procainamide perturbs cellular membranes, which might result in binding of β 2 -GPI and expression of neoepitopes.…”
Section: Antiphospholipid Antibody Development After Infectionmentioning
confidence: 99%